Healthy lifestyle moderates the association between recent negative life events and depressive symptoms: a cross-sectional study - Yang, Yang; Liao, Yuhua; Li, Yanzhi; Zhang, Huimin; Liu, Yifeng; Shi, Guangduoji; Hao, Jiejing; Chen, Ruiying; Xu, Ye; Xin, Zhiyao; Yiming, Subinuer; Wang, Wanxin; et al. (Frontiers in Public Health, 2025)
BackgroundBoth recent negative life events (RNLEs) and lifestyle factors were associated with depressive symptoms, but it is unclear whether adopting a healthy lifestyle can mitigate the association between RNLEs and depressive symptoms. We aim to explore the modifying role of adopting a healthy lifestyle in the association between RNLEs and depressive symptoms.MethodA cross-sectional study was conducted among 4,278 participants aged 18–70 years. RNLEs includes 12 common negative life events that have occurred in the past year, and were classified as low RNLEs (0 RNLEs), intermediate RNLEs (1–5 RNLEs), and high RNLEs (6–12 RNLEs). A healthy lifestyle score in adulthood was constructed as the sum of five modifiable lifestyle factors (i.e., smoking status, drinking status, regular physical activity, sleep duration, and living alone), and was classified as unfavorable [0–2 points], intermediate [3 points], and favorable [4–5 points] groups. Depressive symptoms were assessed using the 9-item Patient Health Questionnaire. A cut-off value of ≥5 was used to identify participants with depressive symptoms.ResultsA total of 1,366 (31.9%) participants had depressive symptoms. Individuals with high RNLEs had a higher likelihood of depressive symptoms (odds ratio [OR] = 8.30, 95% confidence interval [95%CI]: 6.72–10.33, p < 0.001) compared to those with low RNLEs. The prevalence of depressive symptoms decreased with the adoption of more favorable lifestyle categories, with the lowest likelihood observed among individuals with a favorable lifestyle (0.35 [0.30–0.41]). The overall lifestyle was observed as significant moderating role on the association between RNLEs and depressive symptoms (OR, 95%CI: 0.61 [0.40–0.95]).ConclusionIn this cross-sectional study, healthy lifestyle act as a moderating role and adopting a greater number of healthy lifestyles was associated with a lower likelihood of depressive symptoms, and mitigated the association between RNLEs and depressive symptoms.